Kidney function in severely obese adolescents undergoing bariatric surgery. (November 2014) - Xiao, Nianzhou; Jenkins, Todd M.; Nehus, Edward; Inge, Thomas H.; Michalsky, Marc P.; Harmon, Carroll M.; Helmrath, Michael A.; Brandt, Mary L.; Courcoulas, Anita; Moxey‐Mims, Marva; Mitsnefes, Mark M.; for the Teen‐LABS Consortium
<x xml:space="preserve">Abstract</x> Objective Determine objective measures of kidney function and analyze factors associated with kidney dysfunction in severely obese adolescents undergoing weight loss surgery were described. Methods Cross‐sectional data from 242 adolescent participants in the Teen‐Longitudinal Assessment of Bariatric Surgery (Teen‐LABS) study before weight loss surgery were analyzed. Kidney status was assessed by measuring urine albumin creatinine ratio to determine microalbuminuria and by calculating serum cystatin C‐based estimated glomerular filtration rate (eGFR) to assess kidney function. Results Mean age and median body mass index (BMI) were 17.1 years and 50.5 kg/m2, respectively; 76% were females and 65% were non‐Hispanic white race. Fourteen percent of the cohort had microalbuminuria, and 3% had macroalbuminuria; 3% had eGFR < 60 ml/min/1.73 m2, and 7.1% had eGFR > 150 ml/min/1.73 m2. In adjusted analyses, female gender and increasing ferritin levels were significantly associated with the presence of microalbuminuria/macroalbuminuria. Increasing BMI and homeostasis model assessment of insulin resistance values were significantly associated with lower eGFR. Conclusions A significant number of severely obese adolescents undergoing weight loss surgery have evidence of early kidney dysfunction. Longitudinal studies following weight loss surgery in these individuals are needed to determine whether these kidney abnormalities are reversible following weight loss therapy.